Raman Spectroscopy Study of Impacted DLC Coatings - Abdollah, Mohd Fadzli bin; Yamaguchi, Y.; Akao, T.; Inayoshi, N.; Umehara, Noritsugu; Tokoroyama, Takayuki (2010)
Raman scattering is an excellent tool to characterize the structure of carbon atoms in diamond-like carbon (DLC). The study of DLC coatings in the sliding conditions has been conducted for a decade using Raman spectroscopy analysis. However, there is still insufficient information about how the structure of DLC coatings changes during repetitive impact. In this paper changes in the structure under 90o repetitive impact at a large number of cycles are presented.